Regional Urban History: A Statistical and Cartographic Survey of Huron and Southern Bruce Counties, 1864-1981 - Dahms, Fred (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1987)
Statistical and cartographie methods were used to trace the evolution of a group of settlements in Huron and Southern Bruce Counties from 1864 to 1981. Despite the fact that the number of settlements ranged from 30 to 95 during the period under consideration, there was remarkable stability among 15 large places which dominated the area economically at all periods. Competition, date of original settlement, location and changes in transport technology accounted for many of the trends observed. Places established early often continued to benefit from the "momentum" created by their size and age, while more recently developed service centres were adversely affected by the adoption of the motor vehicle and by rural depopulation. The study of a group of settlements over a long time period facilitated explanations of the evolution of individual places.